Analisis Implementasi dan Hambatan Tindak Lanjut Komplikasi PTM Pada Pelaksanaan Posbindu PTM di Wilayah Dinas Kesehatan Kabupaten Sidoarjo - Widarti, Luluk; Sulystiono, Dony; Muhammad Afif Hilmi Masyfahani; Maemonah, Siti (Rena Cipta Mandiri, 2025)
The implementation of NCD Management Posts plays a strategic role in early detection and follow-up of risk factors and complications, but its implementation is often hampered by various obstacles, resulting in suboptimal follow-up of complications. This study aims to analyze the implementation and identify barriers in the follow-up of NCD complications in the implementation of the Management Posts. The research method uses a qualitative design with a phenomenological approach through in-depth interviews with cadres, health workers, and program managers, as well as observation of the Management Posts service flow. The results showed that the implementation of follow-up on NCD complications was still inconsistent due to the limited competence of cadres, the lack of an integrated referral system, suboptimal recording and reporting, and minimal support in terms of facilities such as screening tools and educational media. In addition, the workload of health workers and low community participation also affect the effectiveness of follow-up. The conclusion of this study states that the implementation of Management Posts in following up on NCD complications still requires strengthening the capacity of cadres, improving the referral system, increasing cross-program coordination, and providing supporting facilities to ensure the sustainability of services and more effective prevention of complications.